Transcranial focused ultrasound targeting the default mode network for the treatment of depression - Schachtner, Jessica N.; Dahill-Fuchel, Jacob F.; Allen, Katja E.; Bawiec, Christopher R.; Hollender, Peter J.; Ornellas, Sarah B.; Konecky, Soren D.; Achrol, Achal S.; Allen, John J. B. (Frontiers in Psychiatry, 2025)
IntroductionUp to 50% of individuals fail to respond to current depression treatments. Repetitive negative thought and default mode network hyperconnectivity are central in depression and can potentially be targeted using novel neuromodulation techniques. This community-based study assessed whether a treatment using non-invasive transcranial focused ultrasound targeting the default mode network can decrease depression symptoms and repetitive negative thought, and improve quality of life.MethodsStudy recruitment began in August 2023 and ended in February 2024. Twenty individuals aged 18 – 50 were enrolled from among 247 screened. Exclusion criteria included history of psychosis/mania, acute suicidality, MRI contraindications, pregnancy, and medical and neurological factors that may complicate diagnosis or brain function. Participants completed up to three weeks of transcranial ultrasound (11 sessions) targeting the anterior medial prefrontal cortex; ten minutes per session. Depression severity (Beck Depression Inventory – II and the Hamilton Depression Rating Scale), repetitive negative thought (Perseverative Thinking Questionnaire), and quality of life (World Health Organization Quality of Life Scale) were outcomes.ResultsThis sample was young (mean 30.4 years ± 10.0), predominantly female (75%), with moderate to severe depression and high comorbidity. Fifty percent of participants endorsed current psychiatric medication use. Ten percent of subjects dropped out of the study due to time constraints. Significant decreases in depression were observed over the course of treatment on self-report, 10.9 (p < 0.001, CI = -13.55, -7.92) and interview depression ratings, 4.2 (p < 0.001, CI = -5.85, -2.62), as well as significant decreases in repetitive negative thought, 8.4 (p <0.001, CI = -10.55, -6.03). Improvements in physical and psychological well-being were also observed over the course of treatment, 7.2 (p < 0.001, CI = 3.64, 10.63) and 11.2 (p < 0.001, CI = 7.79, 14.49), respectively, as well as improvements in environment satisfaction, 5.0 (p =0.001, CI = 2.24, 7.56). DiscussionNon-invasive transcranial focused ultrasound holds promise as a treatment for depression holds promise as a treatment for depression, however, future work including control arms is required to ascertain its causal role in depression.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT06320028intr=Ultrasound&cond=depression&locStr=Arizona&country=United%20States&state=Arizona&rank=1, identifier NCT06320028.